Use of Open Access Publishing by Researchers an Analysis of Open Access Availability of Research Literature in the field of Digital Library - Nazim, Mohammad; Zia, Sana (DESIDOC Journal of Library & Information Technology, 2020)
This paper aims to examine the availability of Open Access (OA) research literature in the field of digital library. In order to analyse the availability of OA research literature in the field of digital library, a search was conducted on Web of Science’s Core collection database on June 11, 2019. In response to a topic search TS = “Digital Library” using the advanced search option, 849 articles were retrieved. Of the 849 articles examined, the details of 26 articles were not found in the Google Scholar. Therefore, 823 articles were selected for further analyses. After examining the Websites of OA articles, they were classified into three categories: gold OA, green OA, and both gold and green OA. Furthermore, all the green OA articles were systematically organised into six groups for the examination of the self-archiving venues used by the researchers for self-archiving. Out of 823 articles analysed, OA versions were found for 64.76 per cent of articles. This study found that 26.68 per cent of OA articles were available through gold OA and 60.39 per cent articles were available through green OA, while 36.53 per cent articles were accessible via both OA journals and self-archiving (gold & green OA). Although researchers used various OA platforms for self-archiving of their research work, publishers’ Websites were found as the most preferred choice for self-archiving of research work by the authors in the field of digital library. Computer Science discipline has the highest share of OA copies available through self-archiving. However, it is important to point out that more than 78 per cent of self-archived articles were found as the final publisher’s PDF versions of the article which publishers never allow for self-archiving.